Production, partial purification and characterization of ligninolytic enzymes from selected basidiomycetes mushroom fungi - Ramanaiah Illuri (Elsevier, 2021)
In recent years, many research on the quantity of lignocellulosic waste have been developed. The production, partial purification, and characterisation of ligninolytic enzymes from various fungi are described in this work. On the 21st day of incubation in Potato Dextrose (PD) broth, Hypsizygus ulmarius developed the most laccase (14.83 × 10−6 IU/ml) and manganese peroxidase (24.11 × 10−6 IU/ml), while Pleurotus florida produced the most lignin peroxidase (19.56 × −6 IU/ml). Laccase (Lac), lignin peroxidase (LiP), and manganese peroxidase (MnP), all generated by selected basidiomycetes mushroom fungi, were largely isolated using ammonium sulphate precipitation followed by dialysis. Laccase, lignin peroxidase, and manganese peroxidase purification findings indicated 1.83, 2.13, and 1.77 fold purity enhancements, respectively. Specific activity of purified laccase enzyme preparations ranged from 305.80 to 376.85 IU/mg, purified lignin peroxidase from 258.51 to 336.95 IU/mg, and purified manganese peroxidase from 253.45 to 529.34 IU/mg. H. ulmarius laccase (376.85 IU/mg) with 1.83 fold purification had the highest specific activity of all the ligninolytic enzymes studied, followed by 2.13 fold purification in lignin peroxidase (350.57 IU/mg) and manganese peroxidase (529.34 IU/mg) with 1.77-fold purification. Three notable bands with molecular weights ranging from 43 to 68 kDa and a single prominent band with a molecular weight of 97.4 kDa were identified on a Native PAGE gel from mycelial proteins of selected mushroom fungus. The SDS PAGE profiles of the mycelial proteins from the selected mushroom fungus were similar to the native PAGE. All three partially purified ligninolytic isozymes display three bands in native gel electrophoresis, with only one prominent band in enzyme activity staining. The 43 kDa, 55 kDa, and 68 kDa protein bands correspond to laccase, lignin peroxidase, and manganese peroxidase, respectively.